THE BRAZILIAN ‘ECOLOGICAL-ICMS’: A PES SCHEME BASED ON DISTRIBUTION OF TAX REVENUE - Bassani, Matheus Linck (PANORAMA OF BRAZILIAN LAW, 2015)
The scope of this legal brief is to analyze the Brazilian legislation concerning the ‘Ecological-ICMS’, the ‘ecological’ State value-added tax imposed on the circulation of goods and services – ICMS. Using a deductive method, it was identified this tax mechanism operates as a type of ‘payment for ecosystem services’ (PES) scheme in practice, offering the possibility to stimulate environmental protection by distributing revenue from ICMS collected by States to Municipalities that promote conservation of ecosystems and biodiversity. This type of measure was motivated by the need to address challenges in providing economic compensation for Municipalities that undertook environmental protection measures in Brazil, and can serve as a form of positive incentive for the conservation and sustainable use of biodiversity.